Prevalence of Gingival Pigmentation and its Association with Age, Gender and Gingival Biotype in a Tertiary Care Hospital in Nepal - Khayamali, Jenisha; Khadka, Rachana; Lamichhane, Simant; Rijal, Arjun Hari (Journal of Nepal Health Research Council, 2025)
Background: While dentistry in the past focused primarily on prevention and treatment of dental diseases, modern dentistry has evolved to place greater emphasis on appearance of teeth, gums, and the overall smile. Since gingival pigmentation significantly impacts a patient’s aesthetics, it has recently become a prominent topic of interest. Objective was to determine the prevalence of gingival pigmentation among Nepalese people in terms of its extent and distribution and to correlate it with age, gender, and gingival biotype. Methods: This cross-sectional analytical study was conducted on Nepalese patients who visited the ‘Department of Periodontology and Oral Implantology’ at Dhulikhel Hospital from June 20, 2024 to September 20, 2024 after obtaining ethical approval. Data was collected via convenience sampling, and intraoral examinations focused on gingival biotype and pigmentation in the anterior labial region, a key aesthetic area. The data was entered into MS EXCEL and analyzed using the latest version of SPSS. Results: Total 380 patients were examined in this study, including 173 (45.5%) males and 207(54.5%) females. Most had pigmentation in the attached gingiva followed by interdental papillae. There was a statistically significant relationship (p<0.05) between gingival pigmentation and the patient’ age, as well as between gingival pigmentation and gingival biotype (p<0.05) However, there was no significant relationship (p=0.59) between gingival pigmentation and the patient’s gender. Conclusions: Knowledge regarding the distribution and extent of gingival pigmentation will be a valuable asset for clinicians during various depigmentation procedures, to choose the most appropriate technique for a particular type of gingival pigmentation. Keywords: Depigmentation; gingiva; gingival biotype; gingival pigmentation.